Prevalencia de sífilis en gestantes, en la Provincia de Trujillo, Región La Libertad 2021-2022 - Sánchez Monsalve, Félix (2023)
The WHO estimates that in 2016 there were 5.6 million new cases of syphilis in adolescents and adults aged 15 to 49 years worldwide, with a global incidence rate of 1.5 cases per 1000 women and 1.5 cases per 1000 men. Syphilis has represented an important challenge for public health in Peru, both due to its high prevalence and the serious neonatal sequelae. The objective of this research was to analyze the prevalence of syphilis in pregnant women who were treated in health establishments in the districts of Trujillo, La Libertad region during the months of September 2021 to May 2022. The methodology of the study was descriptive cross-section, in which 66 records of pregnant mothers of different age groups who underwent a diagnosis of syphilis with non-treponemal and treponemal tests were analyzed, identifying reactive and non-reactive pregnant women to syphilis in a spatial distribution in a period After 09 months of data collection, 66 pregnant women were selected, all pregnant women underwent RPR screening tests and TPHA confirmatory tests, all of them met the selection criteria. Data were recorded in an Excel database and analyzed using the SPSSv25 statistical program. For the descriptive analysis, frequencies and percentages were used. The results obtained were a prevalence of 93.9% of pregnant women positive for syphilis which were confirmatory with the TPHA test, 6.1% of pregnant women were non-reactive with RPR and the same percentage were negative with confirmatory TPHA tests. We can conclude that the prevalence of syphilis in pregnant women who attended health establishments in the districts of the province of Trujillo is increasing. The highest prevalence of pregnant women with syphilis were Young, followed by Adults and to a lesser extent were Adolescents. Through this study, it was verified that syphilis continues to be an important public health problem during pregnancy, and that women with syphilis present a greater risk of suffering abortions resulting in fetal death if they are not detected in a timely manner..